EFFECT OF OPERATIONS STRATEGY THROUGH COMPETENCE OF COMPETITIVE ADVANTAGE SMEs ACTORS OF CULINARY NORTH BANDUNG - Asep Kurniawan; Andri Irawan (Prosiding International conference on Information Technology and Business (ICITB), 2018)
MSME actors should have an operating strategy by taking into account the opportunities that are immediately utilized. Many of the competency constraints possessed by MSMEs include the low level of managerial ability that makes their businesses not develop. This is due to the low implementation of the operating strategy so that competitive advantage is difficult to obtain. Competitive advantage is an important thing and can be used as capital for SMEs to continue to grow and develop. This will encourage the need to improve the competencies of MSME actors to be able to implement operating strategies. The purpose of this study was to determine the effect of entrepreneurial competence through an operational strategy on competitive advantage. The research method used uses quantitative methods. The study population was culinary MSMEs in North Bandung with a sample of 50 respondents. The sampling technique used uses probability sampling. Data withdrawal techniques through questionnaires with Likert instrument measurement scale. While the data analysis technique uses Partial Least Square-Structural Equation Modeling. The results of the study showed that the influence of competence on the operating strategy (39.6%) was greater when compared to the influence of competence on superiority (35.3%). Furthermore, the influence of competencies on competitive advantage through operating strategies is 43.1%. This shows that the high and low competitive advantage is determined by the high and low level of entrepreneurial competency which is supported by the high and low operating strategies carried out by MSME players. Keywords : Compotence, Operation Strategy, and Competitive Advantage